Nutrition-sensitive food system in Vietnam’s Mekong Delta: A literature review - Nabuuma, Deborah; Hoang, Ky; Duong, Thanh; Huynh, Tuyen (2023)
Nutrition-sensitive agri-food systems is an approach that puts nutritionally rich foods and dietary diversity at the heart of overcoming undernutrition, overnutrition, and micronutrient deficiencies. A desk review of literature and databases in Vietnam was conducted to identify existing knowledge, gaps, and opportunities for deltaic food systems transformation towards healthy diets. The study was conducted under the OneCGIAR Initiative on Securing the food systems of Asian Mega-Deltas for climate and livelihood resilience (AMD), particularly work package 2 that seeks to ensure that deltaic food systems sustain and enhance nutrition security equitably, in a context of rapid change.